On the Origins and Significance of the Limit Demarcating Low-Enriched Uranium from Highly Enriched Uranium. Issue 2 (3rd May 2016) - Brown, Andrew; Glaser, Alexander
ABSTRACT: The International Atomic Energy Agency (IAEA) defines uranium with a 235 U isotope concentration of 20 percent as the threshold between low-enriched uranium (LEU) and highly enriched uranium (HEU), and as a significant waypoint on the path towards weapon-grade uranium (typically above 90 percent 235 U enrichment). The distinction between LEU and HEU is widely used in shaping nonproliferation policy, and it has featured prominently in commentary over Iran's nuclear program and the series of Nuclear Security Summits that since 2010 have sought to minimize civilian stockpiles and use of HEU. Yet the origin of this threshold is obscure, dating back 6 decades. This research note traces the political origin and the technical basis for this limit.